Images of women in the novels of Ihsan Abdul Quddus and D.H. Lawrence - Gburi, Farooq Saad Jumaah (2016)
The current research aims at studying the literary works of Ishan Abdul Quddus (Arabic writer) and D.H Lawrence (English writer) through the textual analysis. The textual analysis is conducted based on the aesthetic comparison and equality to stand on the negative and positive areas of beauty in terms of language, style and in dealing with the image of women between the two writers. The significance of the research represents in the image of society stand out through the image of women that is considered a part of this society and as the largest share depending on the selecting novels as samples from elected texts that achieve the aim of this research. Therefore, the current research relies on the analysis of the image of women that are embodied by the characters in the novels, where this direction in the literary analysis adopts the term "human sample" in the study of the element of (women) that forms the human existence and the essence of each literary work. The descriptive, analytic approach of this study is based on the descriptive study of woman that deals with her image in terms of beauty, style and language. In this study, the comparative approach highlights the strength and weak points to both writers throughout the image of women as well as the similarities and differences between them. Thus, the researcher acquires the initial outcomes to study the research. This study produces the follies results of head of the family when he caused the disintegration of the family, as well as a mother who wanted to take over her child with all her feelings, causing and establishing him Oedipus complex. Both writers were very conservatively dealt by the society, and the central character they deal in their literary work is the woman. Their literary works, submitted to the present study, were issued that came echo of that selfanxious and worrying and this is literary honest with reality. The good woman neither regards as who perceived by a purely goodness nor the snake woman who perceived by a purely evil, nor a woman of history who perceived by a picture hanging on a wall, but the new woman who reflects what our contemporary society had achieved of evolution as a result to its connection with the civilized world around us. She is the daughter of the new society to all provided her with civilization, culture, freedom and starting. However, both novelists were influenced by the romantic doctrine in the portrayal of women and realism problems. The researcher of the current study finds out that Lawrence D.H is a prominent novelist, poet and critic. Most of his novels were written by using prose, emotional, sentimental, lyric and sensational style. He had the ability to transfer sense at its definite time and place. In addition, his writings reflect complex character stirs up its inside emotions and aspirations enriching the events and characters of his novels. In contrast, while Quddus is critic, playwriting and journalist, his writings tend to be simplicity and to the colloquial language usage.